Application of Chebyshev’s inequality in the preliminary feasibility study for constructing a solar thermal power plant - Pupčević, Milan B.; Mitrović, Zoran D. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: This paper examines some of the applications of Chebyshev’s inequality. Using Chebyshev’s inequality, the analysis of a preliminary feasibility study for constructing a solar thermal power plant in the Banja Luka area has been conducted. The goal of the preliminary analysis is to show, without financial investments, if there is a basis for the climate parameters measurement in the area.Methods: For the known values of the arithmetic means and the standard deviations of the number of cloudy days, the probability of deviation of the number of cloudy days from the mean value was defined by applying Chebyshev’s inequality.Results: The diagram shows the values of the upper and lower limits of the number of cloudy days that deviate from the expected value with a probability of 50%.Conclusion: The preliminary assessment of the justification of the realization of a solar thermal power plant justifies the measurements necessary for the analysis and detailed calculation of this type of a plant, because the annual interval of cloudy days is from 94 to 164, or from 26 to 44% in the year.
Keywords: probability; random variable; dispersion; mean value; cloudy day; solar radiation; solar thermal power plants